Training on Teaching Module Development Based on the Implementation of Technology-Integrated Independent Curriculum for Madrasah Aliyah Teachers - Fitrah Asma Darmawan; Mustamin Mustamin; Saharuddin Saharuddin (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
The Community Partnership Programme (PKM) activities were carried out in Bangkala sub-district, Jeneponto district, South Sulawesi Province, the partners in this PKM activity were Madrasah Aliyah (MA) teachers in Bangkala District, Jeneponto Regency. The objectives of this activity are to: a) Increase the knowledge of madrasah aliyah teachers related to IKM-based teaching modules b) Train partners related to the development of IKM-based teaching modules. The method of implementation is by discussion, lecture and workhop. This activity was carried out to a group of 15 partners and then evaluation and monitoring were carried out regularly for 3 months. The outputs obtained are: 1) Increased partner knowledge related to IKM-based teaching modules; 2) Partners are able to develop IKM teaching modules